Frequency of Left Bundle Branch Block in Patients with Acute Myocardial Infarction; A Cross-Sectional Study - Niknam, Reyhaneh; Mohammadi, Mahmonir (Galen Medical Journal, 2019)
Background: Cardiovascular disease (CVDs) is important problems in both developing and developed countries. Currently, non-invasive methods for diagnosis of CVD, especially myocardial infarction (MI), is an interesting subject in the cardiology field. Some evidence showed left bundle branch block (LBBB) is more prevalent among patients with MI. Hence, this study aimed to investigate the frequency of LBBB and their contributing factors in patients with MI. Materials and Methods: In this cross-sectional study, 150 patients with ST elevation or non-ST elevation on their admission electrocardiography who referred to Boo-Ali and Amir-Al-Momenin hospitals, Tehran from January 2016 to June 2017 entered the study. Frequency of LBBB and right bundle branch block (RBBB) in participants and the contributing factors were determined. Results: In this study, of 150 cases (mean age: 60.35Â±12.88 years), 109 (72.7%) were male, and 41 (27.3%) were female. Out of 150 cases, 12 (8%) had LBBB, 5 (3.3%) RBBB, and 133 (89.7%) had not RBBB or LBBB. Contributing factors were family history, hypertension, and history of ischemic heart disease (P<0.05). Conclusion: Eight percent of patients with myocardial infarction would develop LBBB, which is related to hypertension, and self and family history of ischemic heart disease. [GMJ.2019;8:e1576]Â 